Sejarah Keterlibatan Perempuan Islam dalam Bidang Ekonomi - Rianawati Rianawati (PSGA LP2M IAIN Pontianak, 2016)
Women were treated poorly in Jahiliyah era before Islam came. However, that condition was slightly different after Prophet Muhammad were born. The history proved that moslem women had affiliated in economics, politics, education, health, even war. Furthermore, the associated and roles of Moslem women historically are told from the story of Siti Khadijah and Qilat Ummi Bani as businesswomen. Besides, there are some figures who are also known as hardworking women; Zainab Binti Jahsy, Ummu Salim binti Malhan, Al-Syifa’, Ummul Mukminin Aisyah binti Abu Bakar ash-shiddiq, and so forth. Therefore, there is no limitation for women to advance their career especially to boost their household finances.